Understanding How Ride-Sharing Services Impacted Local Taxi Operators: The Case of Uber in Kuala Lumpur, Malaysia - Kasim, Azilah; Chin, Lim Tong; Hisham, Adnan; Shamsuddin, Shamsul (UUM Press, 2021)
The introduction of ride-sharing alternative to taxis brought a refreshing alternative to consumers because it promises a comfortable and reliable service of ride sharing. However, Uber i.e. the first ride-sharing service offered in Malaysia in particular, has caused uneasiness among the conventional taxi concessionaires. This paper took a case study approach to understand the reasons behind this issue within the context of Kuala Lumpur, Malaysia using document analysis and semi structured interviews. The findings suggest that high quality ride experience that ride- sharing services such as Uber offer have caused much disruption to traditional taxi drivers’ livelihood. Hence, government assistance to improve traditional taxi service is essential to help their continued survival. A few managerial implications are proposed at the end of this paper.